(untitled) (CIPEEX, 2026)
Veratric acid is a phenolic metabolite present in several plant species. Although phenolic compounds are widely studied for their biological activities, veratric acid remains underexplored, particularly regarding its therapeutic potential. Therefore, this study aimed to review the scientific literature to identify the pharmacological and toxicological properties of veratric acid. To this end, a search was conducted in PubMed, ScienceDirect, Scopus, SciELO, and Google Scholar, prioritizing publications published between 2015 and 2025 in Portuguese and English. Experimental studies (in vitro and in vivo) and in silico predictive analyses were included, excluding articles without relevant data or duplicates. In silico analyses indicated low toxicity and compliance with Lipinski’s rule. Experimental studies have shown significant antioxidant activity and anti-inflammatory effects in animal models, although these are still limited. However, clinical trials are scarce, limiting the translation of the findings into therapeutic practice. Thus, veratric acid has a promising pharmacological profile, but clinical evidence is lacking. Future research should expand studies on toxicity, pharmacodynamics, and innovative formulations, targeting its pharmaceutical and nutraceutical uses.